Quality management in government: theory and practice - Agnihotri, V. K.(ed.) (New Delhi, 2003)
Quality as a concept has been widely used in the private sector for improving the performance of organizations. In its initial stages it was applied only to the manu facturing sector, but subsequently it spread to the service sector.
Keywords: Total Quality Management